Effects of Burning Crude Oil Spilled Onto Six Habitat Types in Alaska - McKendrick, Jay D.; Mitchell, WM. W. (ARCTIC, 1978)
The effects on vegetational recovery of removing spilled Prudhoe Bay crude oil from terrestrial sites by burning were observed at three Alaskan locations; Palmer, Fairbanks, and Prudhoe Bay. Five habitat types were studied: 1) abandoned agricultural grass field, 2) the high-brush stage in the secondary succession of interior Alaskan spruce forests, 3) sedge meadow, 4) spruce forest, and 5) wet and mesic arctic tundra. Oil burning was carried out on snow during winter, during the summer growing season and in autumn as soils were freezing. Burning in summer during the growing season was much more detrimental to plant survival than winter burning. Significant amounts of dormant or near dormant vegetation survived hot burns in September where the soil was frozen to a depth of at least four centimeters. Burning spilled oils on frozen soil surfaces at all three locations affected subsequent plant survival less than when soil surfaces were thawed. Plant dormancy, reduced soil permeability, high soil moisture levels and low soil temperatures were the most probable factors contributing to plants surviving oil spills and burns. Heating during the burn failed to raise soil temperatures to levels in the upper soil zone lethal to the perennating buds of grasses and forbs. Spilled oil, permitted to stand (aged), ignited with difficulty or not at all, suggesting the effects of volatilization on combustion potential. Oil that soaked into surface mats of organic matter was also impossible to burn. Attempts to ignite oil spilled on snow during winter at Prudhoe Bay were unsuccessful, possibly because strong winds were rapidly removing volatile fractions. Certain herbaceous plants were relatively unharmed, either by the oil or burning when dormant. Limited damage occurred in winter if the oil was burned immediately after spilling. Delaying burning of oil either 48 hrs or one month after spilling significantly decreased plant survival. In woody vegetation types, plant survival improved slightly where oil was removed by burning. ...